Pengaruh Literasi Keuangan Syariah Terhadap Pengelolaan Keuangan Pribadi Mahasiswa Febi - Farid Maulana; Marcelino Rizki Suryanto; Syifa Aulia Khaerunnisa; Wahyu Hidayat; Hadi Peristiwo; Fitri Fitri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to explore the influence of Islamic financial literacy on the personal financial management of students at the Faculty of Economics and Islamic Business (FEBI) at UIN Sultan Maulana Hasanuddin Banten. Using a causal quantitative method, the study involved a randomly selected sample of 49 FEBI students. Data were collected through questionnaires and analyzed using linear regression analysis. The results showed that Islamic financial literacy has a significant impact on students' personal financial management. Good financial literacy helps students make wiser financial decisions, avoid uncontrollable debt, and achieve financial stability. This study also provides practical implications for educational institutions to enhance their curricula to better address Islamic financial literacy.